Reduce Muscle Fibrosis through Exercise via NRG1/ErbB2 Modification in Diabetic Rats - Majid Amani; Masoud Rahmati; Mohammad Fathi; Hasan Ahmadvand (Journal of Diabetes Research)
Diabetic myopathy refers to the manifestations in the skeletal muscle as a result of altered glucose homeostasis which reflects as fibrosis. Since physical exercise has been indicated a protective strategy for improving glucose metabolism in skeletal muscle, we tested a hypothesis under which the endurance exercise training could reverse the produced skeletal muscle fibrosis by diabetes. Eight-week-old male Wistar rats were randomly assigned into four groups including healthy control (HC), healthy trained (HT), diabetic control (DC), and diabetic trained (DT) groups. Diabetes was induced by a single intraperitoneal injection of streptozotocin (STZ; 45 mg/kg). Rats in the HT and DT groups carried out an exercise program on a motorized treadmill for five days a week over six weeks. Skeletal muscle levels of NRG1and ErbB2 were measured by the Western blot method. Exercise training decreased blood glucose levels in the DT group. Induction of diabetes increased skeletal muscle fibrosis in both the fast extensor digitorum longus (EDL) and slow soleus muscles, while endurance training modified it in diabetic trained rats. Moreover, muscle NRG1and ErbB2 levels were increased in diabetic rats, while training modified muscle NRG1and ErbB2 levels in diabetic trained rats. Our study provides novel evidence that endurance training could modify skeletal muscle fibrosis through NRG1/ErbB2 modification in STZ-induced diabetic rats.